2014
DOI: 10.2147/ijn.s54346
|View full text |Cite
|
Sign up to set email alerts
|

Zerumbone-loaded nanostructured lipid carrier induces G2/M cell cycle arrest and apoptosis via mitochondrial pathway in a human lymphoblastic leukemia cell line

Abstract: This investigation evaluated the antileukemia properties of a zerumbone (ZER)-loaded nanostructured lipid carrier (NLC) prepared by hot high-pressure homogenization techniques in an acute human lymphoblastic leukemia (Jurkat) cell line in vitro. The apoptogenic effect of the ZER-NLC on Jurkat cells was determined by fluorescent and electron microscopy, Annexin V-fluorescein isothiocyanate, Tdt-mediated dUTP nick-end labeling assay, cell cycle analysis, and caspase activity. An MTT (3-(4,5-dimethylthiazol-2-yl)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 16 publications
6
22
0
Order By: Relevance
“…On the other hand, apoptotic cells with condensed chromatin and affected cell membrane, which resulted in clumps of intense green fluorescent spots within the cell. Similar results to this current study were found by Rahman et al and Namvar et al [ 33 , 34 ].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…On the other hand, apoptotic cells with condensed chromatin and affected cell membrane, which resulted in clumps of intense green fluorescent spots within the cell. Similar results to this current study were found by Rahman et al and Namvar et al [ 33 , 34 ].…”
Section: Resultssupporting
confidence: 93%
“…These results suggested that ZnO-NPs could block the cell cycle and induce apoptosis and death in WEHI-3 cells time-dependently in vitro . Simultaneously, our results corroborated with those of Rahman et al and Namvar et al [ 33 , 34 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This work overcame the limitation of applying the CEO to aqueous-based foods. 26 Currently, various novel and innovative NLC have been produced as a carrier to target anticancer functions such as zerumbone, 27 thymoquinone 28,29 and citral 30 and as a worthy drug observably increased antitumor activity in leukemia and breast tumor cells in vitro and in vivo. More examples of compounds loaded NLC are presented in Table 1.…”
Section: Nanocarriermentioning
confidence: 99%
“…Application of NLCs in cancer chemotherapy may result in the improved therapeutic index of loaded anti-cancer agents (72). Besides application for tumor targeting, NLCs as sustained-release drug carrier systems have been represented as promising nanoformulations against the ischemic neural injuries, fungal infections, and leukemia (73)(74)(75)(76)(77)(78).…”
Section: Lipid Nanoparticlesmentioning
confidence: 99%